WASHBACK TO LANGUAGE TEACHERS: A REVIEW OF MODELS AND EMPIRICAL RESEARCH IN AND BEYOND VIETNAM - Thu, Dinh Minh (VNU Journal of Foreign Studies, 2020)
Washback, i.e., test effects on teaching and learning, has been emerging as an attractive research topic in language training and assessment for over the past 20 years for its significant implications of test validation and fairness for both policy-makers and practitioners. Presently, it deserves more Vietnamese researchers’ interest in the context of the enactment of the National Foreign Language Project 2020 (extended to 2025), which puts language assessment as a key innovation requirement. Washback operates either positively or negatively; i.e. promoting or inhibiting learning. Teachers are considered the precursor in the washback mechanism. There is only one washback model on the washback effects on teachers, which is proposed by Shih (2009). This paper aims to critically browse other washback models besides Shin’s (2009) to generate a washback framework on teachers’ perceptions and practices. Previous empirical washback research on teachers in and beyond Vietnam is, then, investigated in alignment with the aspects illustrated in the framework to point out achievements and gaps in the field. A qualitative approach of document analysis of over forty studies of differing types, i.e. books, dissertations and articles, has been adopted to reach the research aim. The discussion is divided into two major parts, including the washback models pertaining to teachers to scaffold a model for teachers’ perceptions and practices, and the results in empirical research in terms of the aspects mentioned in the model. Findings show that washback on teachers’ perceptions ranges from perceptions of the test itself, students’ language ability, teaching contents and methodology to teachers’ professional development. Plus, washback on teachers’ practices concerns their selections of teaching contents and methodology in class as well as their involvement in professional development. The element of professional development can be considered a new light in the reviewed washback model. This has a significant meaning by raising teachers’ awareness of developing themselves professionally. The current paper expects to contribute to elaborating the scenario of washback research for interested researchers, practitioners and policymakers not only in but beyond the context of Vietnam.